2022
DOI: 10.18502/ijrm.v20i1.10411
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum to “Effect of granulocyte colony stimulating factor (G-CSF) on IVF outcomes in infertile women: An RCT” [Int J Reprod BioMed 2016; 14: 341-346]

Abstract: This is a Corrigendum to “Effect of granulocyte colony stimulating factor (G-CSF) on IVF outcomes in infertile women: An RCT” [Int J Reprod BioMed 2016; 14: 341-346] and does not have an abstract. Please download the PDF or view the article HTML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a study conducted by Eftekhar and colleagues, they investigated cases of recurrent implantation failure despite normal endometrial thickness and found that intra-uterine infusion of G-CSF did not increase endometrial thickness or significantly improve pregnancy rates [18].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Eftekhar and colleagues, they investigated cases of recurrent implantation failure despite normal endometrial thickness and found that intra-uterine infusion of G-CSF did not increase endometrial thickness or significantly improve pregnancy rates [18].…”
Section: Discussionmentioning
confidence: 99%